2003
DOI: 10.1262/jrd.49.513
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Ovulation Synchronization Protocol in Anestrous and Cycling Beef Cows

Abstract: Abstract. Applicability of ovulation synchronization protocol using GnRH and PGF2α (PGF) injection to anestrous beef cows remains controversial. We compared the effectiveness of the protocol in the anestrous stage of the beef cow with that in the cycling stage using the same animals. Ovaries of five Japanese Black and three Japanese Shorthorn cows were ultrasonographically examined, and blood samples were collected daily for hormonal analyses. Each animal received the protocol twice (Day -6 to -8: GnRH, Day 0:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…This protocol is designed such that the plasma estradiol-17β concentration at the time of GnRH injection in the cow is as high as that in the cow at estrous. However, the average value in this study was lower than that reported previously [18]. This result suggests that the 36-h interval between PRID removal and GnRH applied in this study was rather short and so the ovulatory follicle had not matured sufficiently by the time of GnRH injection.…”
Section: Discussioncontrasting
confidence: 83%
“…This protocol is designed such that the plasma estradiol-17β concentration at the time of GnRH injection in the cow is as high as that in the cow at estrous. However, the average value in this study was lower than that reported previously [18]. This result suggests that the 36-h interval between PRID removal and GnRH applied in this study was rather short and so the ovulatory follicle had not matured sufficiently by the time of GnRH injection.…”
Section: Discussioncontrasting
confidence: 83%
“…Moreover, the addition of a progesterone-releasing device (a controlled internal device release, CIDR) between days 0 and 7 of the CO-Synch protocol was associated with a higher pregnancy rate (58%) than in cows that lacked a CIDR (48%) [9]. However, another study showed that the prolonged postpartum anestrus limits the efficacy of such synchronization ovulation protocols in Japanese beef cows [14].…”
Section: Introductionmentioning
confidence: 99%
“…Complete uterine involution takes more time than ovarian function, and the uterus is usually not ready for the embryo to implant until approximately 5 weeks postpartum in cows. When the ovaries start functioning normally, and uterine involution becomes complete, some cows can conceive by artificial insemination (AI) after estrous detection or a timed AI protocol without estrous detection [ 3 , 4 , 5 , 6 , 7 , 8 ]. However, some other cows cannot get pregnant because the uterine environment is not yet ready to accept the embryo for implantation because of persistent intrauterine inflammation beyond the puerperium.…”
Section: Introductionmentioning
confidence: 99%